High-fat diet combined with dextran sulfate sodium failed to induce a more serious NASH phenotype than high-fat diet alone - Zhou, Yan; Feng, Ya; Yang, Lili; Zheng, Peiyong; Hang, Lu; Jiang, Fengru; Yuan, Jianye; Zhu, Lixin (Frontiers in Pharmacology, 2022)
Background and Aims: Animal models are essential tools to investigate the pathogenesis of diseases. Disruption in the intestinal epithelial barrier and gut vascular barrier is an early event in the development of non-alcoholic fatty liver disease (NAFLD). Intestinal epithelial barrier can be destroyed by dextran sulfate sodium (DSS) oral administration. High fat diet (HFD)-induced non-alcoholic steatohepatitis (NASH) rat model has been widely used. Recently, the combination of HFD with DSS induced NASH model has also been reported. The present study aimed to evaluate whether this composite NASH animal model is more ideal than that induced by HFD alone. Methods: Rats were divided into control, HFD and HFD combined with DSS (DSS + HFD) groups. They were fed with routine diet, high-fat diet, and HFD combined with DSS drinking, respectively, for 22 weeks. Histopathological analysis (HE staining, Oil-Red O staining, Masson staining), lipid parameters testing (TG, TC, GLU, NEFA, TRIG, LDL, HDL), testing on indicators of inflammation (TNF-α, ALT, AST, ALP, LDH) and oxidative stress (MDA, SOD, CAT) were performed. Results: Rats in HFD and DSS + HFD group displayed increase in the body weight, liver weight, lipids accumulation and the levels of TNF-α, ALT, AST, ALP, MDA in serum and liver accompanied with impaired glucose tolerance, obvious hepatitis, and decreased levels of SOD and CAT in serum and liver compared to those in control group. Moreover, in the DSS + HFD group, but not in the HFD group, proliferation of fibrous tissue in the portal area and the hepatic lobules was found. Conclusion: The addition of DSS on high-fat diet did not exacerbate lipid accumulation and inflammation, but induced NASH-related liver fibrosis.